Pilkada Langsung dan Pendalaman Demokrasi - Lay, Cornelis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2007)
This article asses the implication of direct local executive election (Pilkada Langsung) toward deepining democracy in Indonesia. Based on rapid appraisal study on the first wave of Pilkada Langsung in Indonesia during 2005, this paper argues that the free, fair and non violence process in the series of Pilkada Langsung to some extent indicates a maturity in Indonesian democraacy. The weakness on regulations and lack of managerial skills of local electoral commissions are still major obstacle that prevent further development of democracy. Furthermore,this paper suggests that Pikada Langsung should be placed not only in procedura; processes but to promote democracy in a more substantive way and as a strategy to develop effective local governance